2015
DOI: 10.17576/3l-2015-2102-04
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Visualisation and Advance Organisers in Reading Multimedia-Based Texts

Abstract: Recent advancements in multimedia systems to integrate text, audio, graphics, and video have created a new interest in using instructional strategies in a multimedia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…It terms of its effectiveness in enhancing reading comprehension, Moriyanti et al, (2019) found that visualization affect students reading comprehension in terms of inferring, details, and main idea. The use of visualization also more effective than non-visualized material because it provides motion that helps the students enhance their understanding (Roohani et al, 2015) Even though it is in the context of online learning, teachers still have to prepare learning materials that are attractive to students (Rasmitadila et al, 2020). Visual-based material is certainly an option that can be used in teaching reading and motivating students to read (Choi & Yi, 2016).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…It terms of its effectiveness in enhancing reading comprehension, Moriyanti et al, (2019) found that visualization affect students reading comprehension in terms of inferring, details, and main idea. The use of visualization also more effective than non-visualized material because it provides motion that helps the students enhance their understanding (Roohani et al, 2015) Even though it is in the context of online learning, teachers still have to prepare learning materials that are attractive to students (Rasmitadila et al, 2020). Visual-based material is certainly an option that can be used in teaching reading and motivating students to read (Choi & Yi, 2016).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Current reading research has shown that several factors contribute to the comprehension of the information, including learners' prior knowledge (Al-Jahwari & Al-Humaidi, 2015;Alptekin & Erçetin, 2011;Kobayashi, 2009), learning style preferences (Li & He, 2016), and instructional and cognitive strategies (Carrillo, 2010;Echeverri & McNulty, 2010;Roohani, 2015).…”
Section: Reading Comprehension In Efl Educationmentioning
confidence: 99%
“…For reading and multimedia, researchers have experimented with the format of visual content in conjunction with pedagogical principles. In their study, Roohani, Jafarpour and Zarei [38] checked reading comprehension in children, comparing multimedia texts with two types of graphics-static and animated-in combination with two types of advanced organizers (pedagogical technique for connecting existing knowledge with new knowledge). Among their findings, these authors found that individuals who visualized the animated elements performed better in comprehension tests.…”
Section: Effects Of Visual Content Characteristics On Comprehensionmentioning
confidence: 99%